Pendampingan dan Penyuluhan Penguatan UKM Pempek Ikan Gabus Palembang Menjadi Kelembagaan Koperasi Kota Palembang pada Masa Pandemi Covid 19 - Jayanti, Nirmala; Nearti, Yuwinti; Syukerti, Nanda (Universitas Nusantara PGRI Kediri, 2023)
UKM during the Covid-19 pandemic experienced a decrease in turnover. As a result of the implementation of restrictions on community activities, many UKM are no longer operating due to the spread of Covid-19. Therefore this PKMS activity aims to help Pempek snakehead fish in Palembang City in overcoming business problems during the pandemic. The Snakehead Fish Pempek UKM that became partners in this activity were the Snakehead Fish Pempek UKM Anita Apriliani and other UKM in the pre-cooperative formation. The stages of the activity are carried out through four activities including 1) holding member meetings/meetings which are held regularly and continuously in order to disseminate information about cooperatives including regarding the concept of cooperatives, cooperative advantages and rules related to cooperatives and the procedures for establishing cooperatives, counseling given to UKM so that they understand cooperatives as a whole, 2) provide assistance to UKM in preparing work programs jointly and carried out by implementers (administrators and business units) in accordance with a joint agreement and at the end of each implementation a participatory evaluation is carried out, 3) compiling written rules/norms agreed upon and adhered to. These rules will be contained in the Cooperative AD/ART as well as the preparation of press reports (special regulations) for rules that have not been included in the ART, 4) the preparation of candidates for cooperative management and supervisors, the vision and mission of the cooperative, the minutes of the cooperative and other supporting files such as the necessary documentation of activities in terms of establishing a cooperative to a notary. The results of the activity show that this activity provides new skills for UKM Pempek Anita Apriliani and other UKM. This can be seen from the formation of a Pre-Cooperative with the name Kembang Putri Dadar Cooperative with a total of 9 UKM. The Pre-Cooperative organizational structure that has been formed consists of a chairman, secretary, treasurer and two supervisors. Pre-Cooperative was formed to make it easier to obtain raw materials, capital and marketing. The formation of the Pre-Cooperative is expected to grow the economy both locally and nationally.